Pengaruh Pelarut, Suhu, dan pH Terhadap Pigmen Antosianin dari Ekstrak Kulit Buah Naga Merah (Hylocereus Polyrhizus): Effect of Solvent, Temperature, and pH on Anthocyanin Pigments from Red Dragon Fruit Peel Extract (Hylocereus Polyrhizus) - Gusti Alamsyah Abdil Almajid; Rolan Rusli; Mukti Priastomo (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Red dragon fruit peel (Hylocereus polyrhizus) is an agricultural waste that contains quite high natural anthocyanin pigments. The purpose of this study was to determine how the effect of solvent, temperature and pH on the total content and stability of anthocyanins from liquid extract of red dragon fruit peel. Extraction of anthocyanins from red dragon fruit peel using maceration method with solvent distilled water, distilled water: acetic acid 10% (1:6), and distilled water: citric acid 10% (1:6) and testing was carried out in the form of anthocyanin stability tests at pH 1, 2, 3, 4, 5 and temperatures 0°C, 10°C, 20°C, 30°C, 40°C, 50°C. The results obtained showed that the use of distilled water:citric acid 10% (1:6) as a solvent resulted in the highest total anthocyanin content with 18.034 mg/200 mg and the results of the anthocyanin stability test showed that it was stable at pH 1, 2, 3 and at temperatures of 10°C, 20°C, 30°C.